2008
DOI: 10.1038/bjp.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nitric oxide deficiency causes muscarinic supersensitivity and reduces β3‐adrenoceptor‐mediated relaxation, causing rat detrusor overactivity

Abstract: Background and purpose: Overactive bladder is a complex and widely prevalent condition, but little is known about its physiopathology. We have carried out morphological, biochemical and functional assays to investigate the effects of long-term nitric oxide (NO) deficiency on muscarinic receptor and b-adrenoceptor modulation leading to overactivity of rat detrusor muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 54 publications
4
39
0
5
Order By: Relevance
“…These results suggest that NO has an inhibitory effect in muscular relaxation both in the bladder and in the urethra of animals with chronic deficiency of NO. As demonstrated in a previous experimental study, the systemic reduction of NO causes detrusor overactivity with a decrease in the functional relaxation of the urethra (4,6). Chronic L-NAME treatment also increased the number of micturition cycles in comparison with control animals.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These results suggest that NO has an inhibitory effect in muscular relaxation both in the bladder and in the urethra of animals with chronic deficiency of NO. As demonstrated in a previous experimental study, the systemic reduction of NO causes detrusor overactivity with a decrease in the functional relaxation of the urethra (4,6). Chronic L-NAME treatment also increased the number of micturition cycles in comparison with control animals.…”
Section: Discussionsupporting
confidence: 66%
“…And the amount of cGMP results from the balance between production (NO) and degradation made by phosphodiesterase are enzymes that can hydrolyze and inactivate cyclic nucleotides. It is known that NO is involved in relaxation of the detrusor, bladder neck, urethra and prostate (6,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was also similar to an organ bath study that evaluated bladder of rats submitted to chronic NO deficiency induced by daily administration of L-NAME. An increased contractile response of the detrusor muscle to muscarinic receptors and reduced relaxation mediated by adrenergic receptors was noted (4). In this study, it was also observed an increase in VT in animals with chronic deficiency of NO similarly to a previous study (18).…”
Section: Discussionsupporting
confidence: 85%
“…A study showed that 4-week treatment with the NO synthase blocker L-Nitroarginine methyl ester (L-NAME) causes in vitro DSM supersensitivity to muscarinic agonists via increase in the levels of [H3]-inositol-phophate, accompanied by reduction of ß3-adrenoreceptor mediated DSM relaxations (4).…”
Section: Introductionmentioning
confidence: 99%